The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1159/000522200
|View full text |Cite
|
Sign up to set email alerts
|

The Difference in the Cytoskeletal Machinery of Growth Cones of Growing Axons and Leading Processes

Abstract: Neuronal migration and axon elongation in the developing brain are essential events for neural network formation. Leading processes of migrating neurons and elongating axons have growth cones at their tips. Cytoskeletal machinery for advance of growth cones of the two processes has been thought the same. In this study, we compared axonal elongating growth cones and leading process growth cones in the same conditions that manipulated filopodia, lamellipodia and drebrin, the latter mediates actin filament-micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Dbn1 over-expression in DRGs and in embryonic cortical neurons results in an increase in axon branches, filopodial protrusions and neurites in vivo and in vitro (Geraldo et al, 2008;Ketschek et al, 2016;Poobalasingam et al, 2022). Additionally, knock down of Dbn1 using RNAi leads to a reduction in filopodia, lamellipodia and axon branching in vitro in several neuronal cell types, including cortical neurons and sensory neurons (Geraldo et al, 2008;Ketschek et al, 2016;Miyata and Hayashi, 2022). To complement these findings and our in vivo results on interstitial axon branching regulators we manipulated layer II/III CNPs in vitro.…”
Section: Dbn1 Over-expression and Loss-of-function Axon Protrusion An...mentioning
confidence: 53%
“…Dbn1 over-expression in DRGs and in embryonic cortical neurons results in an increase in axon branches, filopodial protrusions and neurites in vivo and in vitro (Geraldo et al, 2008;Ketschek et al, 2016;Poobalasingam et al, 2022). Additionally, knock down of Dbn1 using RNAi leads to a reduction in filopodia, lamellipodia and axon branching in vitro in several neuronal cell types, including cortical neurons and sensory neurons (Geraldo et al, 2008;Ketschek et al, 2016;Miyata and Hayashi, 2022). To complement these findings and our in vivo results on interstitial axon branching regulators we manipulated layer II/III CNPs in vitro.…”
Section: Dbn1 Over-expression and Loss-of-function Axon Protrusion An...mentioning
confidence: 53%
“…Moreover, axon elongation is inhibited when the molecular interactions of F-actin and microtubules are disrupted 7,8 , indicating that cytoskeletal regulation in growth cones is essential for axon elongation.Migrating neurons have been observed to form a growth-conelike structure (GCLS) at the tips of the leading process 9 . In vitro experiments have suggested that filopodia and lamellipodia of migrating neurons are similar to those of axonal growth cones, though the molecular mechanisms mediating cytoskeletal remodeling in these GCLSs may be distinct from those operating in axonal growth cones 10 . GCLSs have been implicated in the generation of the traction force required for the migration of cultured cerebellar granule cells 11,12 , suggesting that they may be functionally important mediators of neuronal migration in vivo.…”
mentioning
confidence: 99%